Strategic planning and the stratification of Chinese higher education institutions. (November 2018) - Hu, Juan; Liu, Hao; Chen, Yingxia; Qin, Jiali
Highlights: This article is based on the Chinese Higher Education Institutions (HEIs) Strategic Planning Survey. It sheds some new insights on investigating strategic planning from the differentiation of Chinese HEIs. It depicts the current practices of Chinese higher education institutions in strategic planning. A comparative analysis was performed on the basis of the differentiations of HEIs through two dimensions. The study concluded that a highly stratified higher education has resulted in China due to the push of Project 98/5 and Project 21/1. Abstract: Strategic planning is an important instrument for university management. This article's objective is to reveal differences in strategic planning among universities at different levels and of different types. The article is based on the Chinese Higher Education Institutions (HEIs) Strategic Planning Survey. The study attempts to understand awareness of strategic planning, the types of strategic plans, the coverage of plan text, the main influential groups in planning and the approach to assess such planning among Chinese HEIs. A comparative analysis was performed on the basis of the differentiations of HEIs through two dimensions. There are four main findings. First, the surveyed HEIs attach great importance to a five-year plan; however, there are differences in terms of formulating a specialized plan and a medium- and long-term plan. Second, the HEIs at the higher level are more ambitious in their respective missions. Third, the university leaders, leading professors, heads of schools, and heads of university offices are the major influencers in all HEIs. Vocational colleges and private HEIs focus more on the roles of students, alumnus, and external specialists. Fourth, vocational colleges and private HEIs appear to be more action-oriented compared with HEIs at other levels and of other types. This study found that private HEIs had certain unique characteristics in strategic planning. The study concluded that a highly stratified higher education has resulted in China due to the push of Project 98/5 and Project 21/1.